المساهمة في تحديد معايير اختيار منظومة الـ VSATs عند استخدامها لربط شبكات الاتصال - علي صادق; احمد علي; حلوم سهاد (Latakia University Journal -Engineering Sciences Series, 2019)
يتضمن البحث دراسة منظومة الـ VSATs (Very Small Aperture Terminal) التي تستخدم لربط شبكات الاتصال وذلك عبر الأقمار الصناعية. تقدم هذه الدراسة تحليل للوصلة الفضائية المستخدمة لنقل الإشارات عند معدلات إرسال مختلفة ((32-64-96-192 Kbps باستخدام طرق تعديل متعددة (BPSK ,QPSK, 8PSK, 16PSK,32PSK) وكيفية اختيار أبعاد الهوائيات بما يضمن تحسين نسبة استطاعة البت إلى استطاعة الضجيج Eb/No والتي تؤدي بدورها إلى تحسين نسبة استطاعة الحامل إلى استطاعة الضجيج C/N . تم التوصل من خلال البحث إلى نتائج تساعد في اختيار أبعاد الهوائيات المستخدمة في منظومة الـ VSATs من أجل معدلات إرسال مختلفة وتقنيات تعديل رقمية مختلفة وذلك من أجل ضمان جودة الإشارة . This research is a study of VSAT systems which are used in connecting Telecommunication Networks by satellite communication system. The study includes a theoretical analysis of satellite link (up and down links) that transports the signals through different rates (32, 64, 96,192 kbps) and modulation (BPSK, QPSK, 8PSK, 16PSK, 32PSK) It also shows how to select antenna diameter to improve the value of energy per information bit to noise density (Eb/No), which in its turn improves the value of carrier to noise ratio (C/N). The research comes up with some conclusions that would help in choosing the best suitable antenna diameter that is used in VSAT systems for different rates and modulation types to improve signal quality.